Susceptibility of human Plasmodium knowlesi infections to anti-malarials - Farrah, A Fatih; Staines, Henry M; Siner, Angela; Mohammed Atique, Ahmed; Lu, Chan Woon; Pasini, Erica M; Kocken, Clemens HM; Balbir, Singh; Cox-Singh, J.; Sanjeev, Krishna (BioMed Central Ltd., 2013)
Background: Evidence suggests that Plasmodium knowlesi malaria in Sarawak, Malaysian Borneo remains zoonotic, meaning anti-malarial drug resistance is unlikely to have developed in the absence of drug selection pressure. Therefore, adequate response to available anti-malarial treatments is assumed.